2021
DOI: 10.1002/cbf.3655
|View full text |Cite
|
Sign up to set email alerts
|

Chronic asthmatic condition modulated the onset of aging in bone marrow mesenchymal stem cells

Abstract: The emergence of an inflammatory condition such as asthma could affect the therapeutic potential of stem cells. Synopsis of previous documents yielded controversial outcomes, leading to a limitation of stem cell‐based therapy in the clinical setting. This study aimed to assess the impact of asthmatic serum on the MSCs aging and dynamic growth in vitro. Rats were divided into control and asthmatic groups randomly. The asthmatic change was induced using OVA sensitization. The asthmatic structural changes are mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, under hypoglycemic conditions cardiomyocytes release high levels of Exo enriched with specific cargo 38,39 . In a study conducted by Almohammai et al, activated Exo biogenesis and secretion were shown in asthmatic rat lungs and BAL 40 . They concluded that increased Exo can be associated with inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, under hypoglycemic conditions cardiomyocytes release high levels of Exo enriched with specific cargo 38,39 . In a study conducted by Almohammai et al, activated Exo biogenesis and secretion were shown in asthmatic rat lungs and BAL 40 . They concluded that increased Exo can be associated with inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 In a study conducted by Almohammai et al, activated Exo biogenesis and secretion were shown in asthmatic rat lungs and BAL. 40 They concluded that increased Exo can be associated with inflammatory responses. More recently, our team found that the inflammatory responses were increased after immune cell recruitment into the lung tissues in a rat model of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic histomorphometry showed that compared with normal bone, ectopic ossified bone had higher metabolic activity, increased bone deposition rate, wider bone suture, and larger number of osteoblasts [ 30 ]. The fate of progenitor cells such as mesenchymal stem cells can be affected by stimulation from microenvironment [ 31 , 32 ], and it has been proved that progenitor cells, inflammation niches and disorder of signaling pathway promote the formation of HO. Based on previous studies of HO related molecular mechanism and signaling pathway, we studied the targeted gene therapy method that may be used for the treatment of HO.…”
Section: Discussionmentioning
confidence: 99%
“…Transplanted MSCs suffer from microenvironmental changes involving hypoxia (21% O 2 in vitro culture, 2%–8% oxygen in the body) 29 , nutrient deficiency 109 , increased levels of oxidative stress 23 , and recruitment of immune cells post-transplantation 110 , all of which hamper the therapeutic potential of MSCs 25 , 111 , 112 . Culturing MSCs in media with hypoxia, inflammatory cytokines, or asthmatic serum to mimic the in vivo microenvironment can improve the survival or therapeutic potential of MSCs.…”
Section: Strategies To Enhance the Therapeutic Effect Of Mscs On Asthmamentioning
confidence: 99%
“…However, MSC-based strategies for asthma treatment are challenging. For example, limited in vitro amplification, gradual loss of stemness, and harsh microenvironments impair the therapeutic potential of transplanted MSCs and impede their prospects for clinical application 22 25 . Over the years, various strategies have been used to improve therapeutic effects by enhancing the properties of MSCs or the local microenvironment to help MSCs survive 26 30 .…”
Section: Introductionmentioning
confidence: 99%